Current Advances In Radiotherapy - Dini Andriani Pramitasari (Conferences of Medical Sciences Dies Natalis, 2019)
Health science and technology continues to develop including in radiotherapy. The use of Stereotactic Radiosurgery (SRS) has already proved to be safe and effective for treating inaccessible intracerebral lesions through operation or chemotherapy. With the principles of therapeutic ratio, SRS is mostly used for arteriovenous malformations, acoustic neuroma, craniopharyngioma, pituitary adenoma, and brain metastase.